STUDI KONSTRUKSI HISTORIS PENDIDIKAN ISLAM ERA KLASIK HINGGA MODERN - M. Mujab (el-hikmah, 2012)
Islamic Education at first period was showed its superiority. It was proved by the emergency of superior, dinamic and creative generation. The generation from companions of the prophet, tabi’in and tabi’it tabiin are a sturdy generation, have a high comitment for moral values of Islam. Whereas on the pre-modern, Islam was suffered a decrease. Its quite alarming setback. Its period of deteriorate. This periode was identified as time of the demise of the Islamic struggle. So, education was not incised achievement then previous generations.